Carbonate cemented artificial sandstone containing corrosion holes and preparation method thereof

By using quartz sand and water-absorbing resin in the model box to simulate dissolving holes and forming dissolving holes through carbonate cementing and drying, the problem of difficult sampling of carbonate cementing rock samples in the deep formation is solved, an efficient and economical sample preparation process is achieved, and physical and mechanical parameters can be effectively controlled.

CN119735412AActive Publication Date: 2025-04-01INSTITUTE FOR SMART CITY OF CHONGQING UNIVERSITY IN LIYANG LIYANG +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411698371.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-01
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing deep strata containing dissolvable pores in carbon sequestration areas are difficult to sample for carbon sequestration research.

Method used

A preparation method is adopted, by filling quartz sand with water-absorbing resin into the model box, carbonate cementing is performed using urease solution and cementing solution to simulate dissolution holes, and rapid dehydration is achieved through drying to form dissolution holes.

Benefits of technology

Compared with drilling sampling, sample preparation costs can be significantly saved, and a large number of carbonate cemented sandstone molding samples with dissolving holes with similar physical and mechanical parameters can be obtained in a short time, and physical and mechanical parameters such as porosity and permeability can be effectively controlled.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735412A_ABST
    Figure CN119735412A_ABST
Patent Text Reader

Abstract

The invention discloses corrosion hole-containing carbonate cemented artificial sandstone and a preparation method thereof, and belongs to the technical field of carbon sequestration and geological mining. The preparation method comprises the following steps: filling quartz sand and water-absorbing resin together to obtain a sample, uniformly mixing a urease solution and a cementing solution to obtain a mixed solution, adding the mixed solution into the sample, standing, discharging the mixed solution, and drying to obtain the urease-based composite material. And repeatedly adding the mixed solution, standing and discharging until the content of the carbonate cement in the sample reaches a target value, and finally demolding and drying. The method adopts enzyme to induce calcium carbonate precipitation to simulate carbonate cement, and adopts the prefabricated corrosion hole model prepared from the water-absorbent resin to simulate the corrosion hole, so that the sample preparation cost can be saved, the sample preparation time is short, and the sample preparation efficiency is high. Physical and mechanical parameters such as porosity, permeability, cement content, number and size of the corrosion holes and the like of the prepared carbonate cemented artificial sandstone containing the corrosion holes can be effectively controlled, and the applicability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon sequestration and geological mining, and in particular to carbonate-cemented artificial sandstone containing dissolution pores and a preparation method thereof. Background Art

[0002] Since the Industrial Revolution, the massive emission of greenhouse gases has led to global warming. CO2 is the main greenhouse gas, accounting for about 82% of greenhouse gases. CO2 geological storage is an effective way to control CO2 emissions and alleviate global warming. CO2 geological storage is achieved by injecting captured CO2 into deep formations. CO2 geological storage sites mainly include saline aquifers, depleted oil and gas reservoirs, unexploited coal seams, basalt and volcanic rock formations, etc.

[0003] At present, there are widespread carbonate-cemented sandstones in carbon storage areas, such as calcite, ferrocalcite, and ankerite. In deep formations, carbonate-cemented salts are prone to form dissolution pores under the combined action of high temperature, high pressure, and formation water. In addition, carbonate cementation strength is weak, the structure is loose, and the cost of on-site sampling is high, making it difficult to obtain a large number of representative rock samples. Therefore, in order to carry out research on CO2 geological storage in carbonate-cemented sandstone reservoirs, it is urgent to propose a method for preparing carbonate-cemented artificial sandstone containing dissolution pores. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a carbonate-cemented artificial sandstone containing dissolution pores and a preparation method thereof, so as to solve the problem that carbonate-cemented rock samples containing dissolution pores in deep strata used for carbon storage areas are difficult to sample for carbon storage research.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] A method for preparing carbonate-cemented artificial sandstone containing dissolution pores comprises the following steps:

[0007] First, quartz sand and water-absorbed resin are loaded together to obtain a sample, urease solution and cementing solution are evenly mixed to obtain a mixed solution, and then the mixed solution is added to the sample and allowed to stand, and then the mixed solution is discharged, and the mixed solution is added, allowed to stand and discharged repeatedly until the carbonate cementing material content of the sample reaches the target value, and finally demolding and drying are carried out to obtain the product.

[0008] Furthermore, the quartz sand is dried at 100-110° C. for 20-30 hours before filling.

[0009] Furthermore, the quartz sand is sieved and washed with ultrapure water before drying.

[0010] Furthermore, the resin is a sodium polyacrylate cross-linked copolymer, which expands in volume by 80-120 times upon absorbing water.

[0011] The beneficial effect of adopting the above-mentioned further technical scheme is as follows: the present invention prepares a prefabricated dissolution hole model by using a water-absorbing resin to simulate the dissolution holes, and realizes rapid dehydration by drying, thereby reducing the volume and forming dissolution holes. Compared with drilling sampling, it can greatly save sample preparation costs.

[0012] Furthermore, the filling is divided into 4 to 5 times, and the hair is scraped between layers.

[0013] Furthermore, the activity of the urease solution is 5 to 25 kU.

[0014] Further, the cementing solution is a mixed solution of calcium chloride, urea and skimmed milk powder;

[0015] Among them, the concentration of calcium chloride is 0.5-2 mol / L, the concentration of urea solution is 0.5-2 mol / L, and the concentration of skimmed milk powder is 2-6 g / L.

[0016] Furthermore, the concentration ratio of calcium chloride to urea is 1:1.

[0017] Furthermore, the volume ratio of the urease solution to the cementing solution is 1:1 to 1:4.

[0018] Furthermore, the amount of the mixed solution added is 1 to 2 times the pore volume of the sample, and the adding time is less than 0.5 h.

[0019] Furthermore, the standing time is 5 to 7 hours.

[0020] Furthermore, the drying temperature is 50-70° C. and the drying time is 40-60 hours.

[0021] A carbonate-cemented artificial sandstone containing dissolution pores is prepared by adopting the preparation method.

[0022] Furthermore, the above-mentioned device for preparing carbonate-cemented artificial sandstone containing dissolved pores comprises a mixed solution container, a model box, a first seepage liquid recovery dish and a second seepage liquid recovery dish;

[0023] The model box is connected to the first exudate recovery dish through a third pipeline, a second valve is arranged on the pipeline, the mixed solution container is connected to the third pipeline through the first pipeline, the connection is located between the second valve and the interface between the third pipeline and the model box, and a first valve and a first peristaltic pump are arranged on the first pipeline;

[0024] The model box is connected to the second exudate recovery dish through a fourth pipe, a fourth valve is arranged on the pipe, the mixed solution container is connected to the fourth pipe through a second pipe, the connection is located between the fourth valve and the interface between the fourth pipe and the model box, and a third valve and a second peristaltic pump are arranged on the second pipe.

[0025] Furthermore, a method for preparing carbonate-cemented artificial sandstone containing dissolution pores using the above-mentioned device for preparing carbonate-cemented artificial sandstone containing dissolution pores comprises the following steps:

[0026] First, a mixed solution consisting of urease solution and cementing solution is loaded into a mixed solution container, and quartz sand and water-absorbed resin are loaded into a model box; then the first peristaltic pump and the first valve are opened to pump the mixed solution into the sand sample in the model box, and after the pumping is completed, the first peristaltic pump and the first valve are closed and allowed to stand; then the first peristaltic pump and the fourth valve are opened to discharge the reacted mixed solution into a second leachate recovery dish; then the second peristaltic pump, the third valve and the second valve are used to pump in the solution for the second time, stand and discharge, and finally the carbonate cementing material content of the sample reaches the target value by alternating injection from left to right, demolding, drying and obtaining the product.

[0027] The beneficial effect of adopting the above further technical solution is: by adopting the method of alternately injecting the mixed solution on the left and right sides, the accumulation of carbonate cements at the injection port can be effectively prevented, thereby effectively improving the uniformity of carbonate cements in the obtained carbonate-cemented artificial sandstone containing dissolution pores.

[0028] The present invention has the following beneficial effects:

[0029] The present invention adopts enzyme-induced calcium carbonate precipitation to simulate carbonate cement, and adopts a prefabricated dissolution hole model made of water-absorbing resin to simulate dissolution holes. Compared with drilling sampling, the sample preparation cost can be greatly saved, and a large number of carbonate-cemented sandstone molded samples containing dissolution holes with similar physical and mechanical parameters can be obtained in a short time. The physical and mechanical parameters such as porosity, permeability, cement content, number and size of dissolution holes of the prepared carbonate-cemented artificial sandstone containing dissolution holes can be effectively controlled, and the applicability is strong. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a structural diagram of a device for preparing carbonate-cemented artificial sandstone containing dissolved pores, wherein: 1-mixed solution container, 2-first peristaltic pump, 3-second peristaltic pump, 4-first pipeline, 5-first valve, 6-third valve, 7-second valve, 8-fourth valve, 9-model box, 10-sand sample, 11-prefabricated dissolved pore model, 12-first seepage liquid recovery dish, 13-second seepage liquid recovery dish, 14-third pipeline, 15-fourth pipeline, 16-second pipeline;

[0031] Figure 2 The CT scanning pore structure diagram of carbonate cemented artificial sandstone containing dissolution pores obtained in Example 1. DETAILED DESCRIPTION

[0032] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0033] Embodiment 1:

[0034] A method for preparing carbonate-cemented artificial sandstone containing dissolution pores comprises the following steps:

[0035] (1) After sieving the quartz sand, wash it with ultrapure water, and then put the washed quartz sand into an oven at 105°C and dry it for 24 hours.

[0036] (2) The quartz sand dried in step (1) was quartzized to a dry density of 1.53 g / cm 3 The samples were weighed and loaded into a cylindrical model box 9 with a diameter of 39.1 mm and a height of 80 mm in four batches. The layers were shaved and the prefabricated dissolution hole model 11 was made by adding a sodium polyacrylate cross-linked copolymer (Shanghai McLean Biochemical Technology Co., Ltd.) whose volume expanded 100 times after absorbing water.

[0037] (3) Prepare a urease solution and adjust the activity to 10 kU; use calcium chloride, urea and skimmed milk powder to prepare a binding solution, the calcium chloride concentration is 1 mol / L, the urea concentration is 1 mol / L, and the skimmed milk powder concentration is 4 g / L; mix the urease solution and the binding solution evenly to obtain a mixed solution, the volume ratio of the urease solution to the binding solution is 1:2, and add the mixed solution into the mixed solution container 1.

[0038] (4) Open the first peristaltic pump 2 and the first valve 5 to pump the mixed solution into the sand sample 10 in the model box 9. After the pumping is completed, close the first peristaltic pump 2 and the first valve 5 and let it stand. Then open the first peristaltic pump 2 and the fourth valve 8 to discharge the reacted mixed solution into the second seepage liquid recovery dish 13. Then, use the second peristaltic pump 3, the third valve 6 and the second valve 7 to pump the solution in for the second time, let it stand and discharge. Finally, alternately inject left and right until the carbonate cement content of the sample reaches the target value of 17.5g. The mixed solution pumping speed is 2mL / min, and the volume of the pumped mixed solution is 1.1 times the pore volume.

[0039] (5) After demoulding and taking out the sample, it was placed in a 60° C. oven for drying for 48 h. The prefabricated dissolution pore model 11 was dehydrated during the drying process, and its volume was drastically reduced, forming dissolution pores, thereby obtaining carbonate-cemented artificial sandstone containing dissolution pores.

[0040] The CT structure of carbonate cemented artificial sandstone containing dissolved pores prepared in this embodiment is shown in Figure 2As shown, the porosity is 32.3%, the permeability is 1057 mD, and the carbonate cement content is 13.6% (mass ratio).

[0041] Embodiment 2:

[0042] A method for preparing carbonate-cemented artificial sandstone containing dissolution pores comprises the following steps:

[0043] (1) After sieving the quartz sand, wash it with ultrapure water, and then put the washed quartz sand into an oven at 105°C and dry it for 24 hours.

[0044] (2) The quartz sand dried in step (1) was quartzized to a dry density of 1.53 g / cm 3 The samples were weighed and loaded into a cylindrical model box 9 with a diameter of 39.1 mm and a height of 80 mm in four batches. The layers were shaved and the prefabricated dissolution hole model 11 was made by adding a sodium polyacrylate cross-linked copolymer (Shanghai McLean Biochemical Technology Co., Ltd.) whose volume expanded 100 times after absorbing water.

[0045] (3) Prepare a urease solution and adjust the activity to 10 kU; use calcium chloride, urea and skimmed milk powder to prepare a binding solution, the calcium chloride concentration is 0.5 mol / L, the urea concentration is 0.5 mol / L, and the skimmed milk powder concentration is 2 g / L; mix the urease solution and the binding solution evenly to obtain a mixed solution, the volume ratio of the urease solution to the binding solution is 1:4, and add the mixed solution into the mixed solution container 1.

[0046] (4) Open the first peristaltic pump 2 and the first valve 5 to pump the mixed solution into the sand sample 10 in the model box 9. After the pumping is completed, close the first peristaltic pump 2 and the first valve 5 and let it stand. Then open the first peristaltic pump 2 and the fourth valve 8 to discharge the reacted mixed solution into the second seepage liquid recovery dish 13. Then, use the second peristaltic pump 3, the third valve 6 and the second valve 7 to pump the solution in for the second time, let it stand and discharge it. Finally, alternately inject the solution left and right until the carbonate cement content of the sample reaches the target value of 16.2g. The mixed solution pumping speed is 2mL / min, and the volume of the mixed solution pumped in is 1.1 times the pore volume.

[0047] (5) After demoulding and taking out the sample, it was placed in a 60° C. oven for drying for 48 h. The prefabricated dissolution pore model 11 was dehydrated during the drying process, and its volume was drastically reduced, forming dissolution pores, thereby obtaining carbonate-cemented artificial sandstone containing dissolution pores.

[0048] Embodiment 3:

[0049] A method for preparing carbonate-cemented artificial sandstone containing dissolution pores comprises the following steps:

[0050] (1) After sieving the quartz sand, wash it with ultrapure water, and then put the washed quartz sand into an oven at 105°C and dry it for 24 hours.

[0051] (2) The quartz sand dried in step (1) was quartzized to a dry density of 1.53 g / cm 3 The samples were weighed and loaded into a cylindrical model box 9 with a diameter of 39.1 mm and a height of 80 mm in four batches. The layers were shaved and the prefabricated dissolution hole model 11 was made by adding a sodium polyacrylate cross-linked copolymer (Shanghai McLean Biochemical Technology Co., Ltd.) whose volume expanded 100 times after absorbing water.

[0052] (3) Prepare a urease solution and adjust the activity to 10 kU; use calcium chloride, urea and skimmed milk powder to prepare a binder solution, the calcium chloride concentration is 2 mol / L, the urea concentration is 2 mol / L, and the skimmed milk powder concentration is 6 g / L; mix the urease solution and the binder solution evenly to obtain a mixed solution, the volume ratio of the urease solution to the binder solution is 1:1, and add the mixed solution into the mixed solution container 1.

[0053] (4) Open the first peristaltic pump 2 and the first valve 5 to pump the mixed solution into the sand sample 10 in the model box 9. After the pumping is completed, close the first peristaltic pump 2 and the first valve 5 and let it stand. Then open the first peristaltic pump 2 and the fourth valve 8 to discharge the reacted mixed solution into the second seepage liquid recovery dish 13. Then, use the second peristaltic pump 3, the third valve 6 and the second valve 7 to pump the solution in for the second time, let it stand and discharge. Finally, alternately inject left and right until the carbonate cement content of the sample reaches the target value of 18.7g. The mixed solution pumping speed is 2mL / min, and the volume of the mixed solution pumped in is 1.1 times the pore volume.

[0054] (5) After demoulding and taking out the sample, it was placed in a 60° C. oven for drying for 48 h. The prefabricated dissolution pore model 11 was dehydrated during the drying process, and its volume was drastically reduced, forming dissolution pores, thereby obtaining carbonate-cemented artificial sandstone containing dissolution pores.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing carbonate-cemented artificial sandstone containing dissolution pores, characterized in that: The following steps are involved: First, quartz sand and water-absorbed resin are loaded together to obtain a sample, urease solution and cementing solution are evenly mixed to obtain a mixed solution, and then the mixed solution is added to the sample and allowed to stand, and then the mixed solution is discharged, and the mixed solution is added, allowed to stand and discharged repeatedly until the carbonate cementing material content of the sample reaches the target value, and finally demolding and drying are carried out to obtain the product.

2. The method for preparing carbonate cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The quartz sand is dried at 100-110° C. for 20-30 hours before filling.

3. The method for preparing carbonate cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The resin is a sodium polyacrylate cross-linked copolymer, which expands in volume by 80-120 times after absorbing water.

4. The method for preparing carbonate cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The activity of the urease solution is 5 to 25 kU.

5. The method for preparing carbonate cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The cementing solution is a mixed solution of calcium chloride, urea and skimmed milk powder; Among them, the concentration of calcium chloride is 0.5-2 mol / L, the concentration of urea solution is 0.5-2 mol / L, and the concentration of skimmed milk powder is 2-6 g / L.

6. The method for preparing carbonate cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The volume ratio of the urease solution to the cementing solution is 1:1 to 1:

4.

7. The method for preparing carbonate-cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The amount of the mixed solution added is 1 to 2 times the pore volume of the sample, and the adding time is less than 0.5h.

8. The method for preparing carbonate-cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The standing time is 5 to 7 hours.

9. The method for preparing carbonate cemented artificial sandstone containing dissolution pores according to claim 1, characterized in that: The drying temperature is 50-70° C. and the drying time is 40-60 hours.

10. A carbonate-cemented artificial sandstone containing dissolved pores, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Analysis method of corrosion action and corrosion effect of carbonate rock

    CN104407118A

  • Calcified ecological brick and production method thereof

    CN108675689A

  • Preparation method of physical simulation sample of hole type carbonate rock reservoir and application

    CN109162709A

  • Porous fly ash unfired ceramsite and preparation method thereof

    CN111620658A

  • Device and method for measuring influence of effective stress on hydrate occurrence state

    CN117451527A